Fluorogenic BODIPY molecular rotor as an apoptosis marker - Ashokkumar, Pichandi; Ashoka, Anila Hoskere; Collot, Mayeul; Das, Amitava; Klymchenko, Andrey S. (Chemical Communications, 2019)
Based on a BODIPY molecular rotor and a zinc-dipicolylamine receptor, we designed a fluorogenic probe for the detection of apoptosis. Being poorly emissive in solution and with healthy cells, it selectively binds phosphatidylserine of early apoptotic cells and internalizes into late apoptotic cells, lighting up its green fluorescence.